Investigating Students’ Difficulties in Reading Academic Text at a Private University in Indonesia - Sumedi, Siti Hanna; Putri, Sonia Archelia (Fakultas Ilmu Budaya, Universitas Brawijaya, 2025)
This study investigated students' difficulties in reading academic texts at a private university in Indonesia. This study aims to investigate students' difficulties in reading academic texts along with its causes, constructive solutions, and effectual recommendation. This study applied qualitative research method specifically case study design. Data were obtained from observation and interview. The data were analyzed using thematic analysis. The participants of this study were fourth-semester students of the English Education Study Program. This study revealed students' difficulties in reading academic text at a private university in Indonesia were: limited vocabulary; unfamiliarity of academic words, readability problem; complexity of academic text structure, lack of reading fluency; difficulty of understanding function word, and inadequate use of reading strategies; insufficient use of skimming and scanning. It was further investigated the students' difficulties in reading academic texts were significantly caused by limited vocabulary knowledge, specifically limited academic vocabulary mastery. The findings derived from this study underscore the critical need to address students' difficulties in academic reading. This study emphasized the importance of equipping students with academic vocabularies lesson or assistance and implementation of metacognitive-based reading strategies to overcome students’ difficulties in reading academic text for better and successful academic reading skill and achievement.